Tengger Communities Creativity and Language Preservation in Text-Speak on the WhatsApp Social Media Platform - Riyanto E.D.; Dwisusilo S.M.; Shaffarullah Abd. Rahman; Afdholy N (EDAP - Angelo Pontecorboli Editore, 2023)
This article aims to figure out the types of creativity from the Tengger community while applying their own language especially in WhatsApp messaging. The Tengger language is extremely threatened due to increased contact with lowlanders who speak the prestige language. The use of text-speak in Tengger Communities is a form of creative expression and innovation that can lead to the development of new forms of Tengger language that reflect the changing needs and realities of these communities. This research aims to inquire the use of text-speak and language preservation among the Tengger Communities in the context of the WhatsApp social media platform. A qualitative technique was applied in this research’s methodology and the data was gathered through interviews and library research. The result showed that there are types of creativity that appear in text-speak of the Tengger community, such as orthographic abbreviation and phonological abbreviation. Each type of creativity represented the way the Tengger community revitalized their indigeneous language. This research will also provide practical guidance and advice for Tengger Communities on how to effectively use text-speak for language preservation while taking into account the specific linguistic and cultural characteristics of these communities. Ultimately, this research promotes linguistic diversity and multiculturalism by showcasing the beauty and richness of the Tengger language and cultural heritage to the wider world.